Cultural Resilience and Syncretism: The Towani Tolotang Community's Journey in Indonesia's Religious Landscape - Tahara, Tasrifin; Al Isra, Andi Batara; Tiro, Surahmat (Journal of Ethnic and Cultural Studies, 2023)
The Towani Tolotang community, nestled in the Sindenreng Rappang Regency of South Sulawesi, Indonesia, stands as a testament to the enduring legacy of indigenous faith and culture. This research, spanning three months from March to June 2023, delves into the community's unique religious practices, challenges, and resilience, shedding light on Indonesia's complex landscape of religious diversity. The Towani Tolotang community's unwavering commitment to their ancestral beliefs, despite being classified under the umbrella of Hinduism by the Indonesian government, exemplifies the resilience of indigenous traditions. Their syncretic belief system, interweaving animism, Hindu rituals, and historical adaptations set them apart within a predominantly Muslim society. Traditional leaders safeguarding their rituals and traditions are critical to cultural preservation. The community's resilience lies in its adaptability, secrecy maintenance, and strategies for transmitting religious knowledge across generations. Challenges persist, with discriminatory policies and interactions with the majority Muslim society. However, the Towani Tolotang community's unwavering commitment to its unique identity serves as an inspiring example of cultural preservation. This research offers valuable insights for scholars, policymakers, and advocates of religious diversity. It unravels the complexities of indigenous faith and its adaptation in a changing world, providing lessons in understanding, tolerance, and cultural heritage preservation. The Towani Tolotang community's story stands as a profound example of how traditions endure, evolve, and flourish amid the currents of history.